Reviews of physiology, biochemistry and pharmacology, Vol. 164 - Nilius, Bernd (Reviews of Physiology, Biochemistry and Pharmacology, 2013)
T. Hara, I. Kimura, D. Inoue, A. Ichimura, and A. Hirasawa: Free fatty acid receptors and their role in regulation of energy metabolism. B. Nilius and G. Appendino. Spices: the savory and healthy science of pungency.